Challenges for first-year undergraduates with a non-EMI background in an EMI classroom: A case study - K. A. Siddiqui (Russian State Vocational Pedagogical University, 2021)
Introduction. English has been the official language as well as medium of instruction (MOI) in higher education of Pakistan for over 70 years despite decolonisation in Asia in 1950s. However, the majority of undergraduates come from non-EMI (English as a medium of instruction) background because MOI in private or public primary and secondary schools is either regional or local language. Therefore, first year undergraduates face challenges in EMI classrooms at university.Aim. This study aimed to investigate the challenges first year undergraduates with nonEMI background face in an EMI classroom in a public sector university in Sukkur, Pakistan.Methodology and research methods. Using the case study approach, six purposively selected participants were interviewed using semi-structured interviews as the data collection tool.Results and scientific novelty. The findings reveal that the learners face issues such as ineffective presentation, incoherent answers in writing, difficult grammatical structures, lack of vocabulary and partial comprehension of content. One of the key findings of the study is the psychological pressure students experience in an EMI classroom. The research is novel in the sense it brings to light language-related issues faced by students such as lack of vocabulary, improper organisation of ideas, and the role of varied language level of books and teachers. Since these challenges have not been explored at undergraduate level, and that too for students from non-EMI background, the study bears great significance for all stakeholders to develop effective strategies for future.Practical significance. The study will have implications for both policymakers and practitioners in higher education of Pakistan.